E-045 Balloon-assisted coiling of cerebral aneurysms with the dual lumen scepter XC balloon catheter: experience at two high volume centers. (22nd July 2018) - Wallace, A; Samaniego, E; Kayan, Y; Derdeyn, C; Delgado, J; Zheng, B; Fease, J; Thomas, M; Scholz, J; Milner, A; Ortega, S
Abstract : Introduction: Balloon-assisted coiling (BAC) is a well-established technique for treatment of wide-necked cerebral aneurysms. The Scepter XC (Microvention, Tustin, California, USA) is a dual-lumen balloon catheter that can be used for aneurysm-neck remodeling, protection of branch vessels arising from or near the aneurysm neck, and stabilization of the microcatheter during coil deployment. The lumen also accommodates a 0.014 inch microwire. We describe our initial experience with the use of this device for BAC of cerebral aneurysms. Methods: Two high-volume institution neurointerventional databases were retrospectively reviewed for cerebral aneurysms treated with BAC using the Scepter XC balloon catheter. Wide-neck aneurysms were defined as those with a neck width ≥4 mm or a dome-to-neck ratio <2 measured on digital subtraction angiography (DSA). Patient demographics, aneurysm characteristics, and procedural details were recorded. Follow-up occlusion status was assessed with time-of-flight MRA for aneurysms <10 mm, MRA with and without gadolinium contrast for aneurysms >10 mm, or DSA and rated using the Raymond-Roy classification. Results: During the study period, 231 aneurysms were treated in 219 patients (152 women, 67 men) with a mean age of 58.4±12.2 years. Mean aneurysm size was 6.1±3.1 mm, with a mean neck diameter of 3.1±1.3 mm. 77.9% (180/231) of aneurysms were wide-necked, and 39.8% (92/231) were acutely ruptured at the time of treatment. The overall complication rate was 12.1% (28/231) per treated aneurysm, including a 4.8% (11/231) rate of symptomatic thromboembolic events, 8.6% (8/92) rate of intraoperative rupture when treating acutely ruptured aneurysms, and 1.4% (2/139) rate of intraoperative aneurysm rupture in elective cases. Excluding patients who died, DSA or MRA follow up was available for 85.3% (191/224) of aneurysms. During a mean follow-up of 17.4±13.0 months (range, 1.7–66.5 months), Raymond-Roy 1oc and 2oc clusion rates were 56.5% (108/191) and 35.6% (68/191), respectively. The retreatment rate was 13% (24/191). Conclusions: Balloon-assisted coiling using the dual coaxial lumen Scepter XC demonstrates acceptable aneurysm occlusion and complication rates. Disclosures: A. Wallace: None. E. Samaniego: 2; C; Medtronic, Microvention. Y. Kayan: 2; C; Medtronic, Penumbra, Microvention. C. Derdeyn: None. J. Delgado: 2; C; Medtronic, Penumbra, Microvention, Accriva. B. Zheng: None. J. Fease: None. M. Thomas: None. J. Scholz: None. A. Milner: None. S. Ortega: 2; C; Stryker Neurovascular, Medtronic.